Multileveled Hierarchical Hydrogel with Continuous Biophysical and Biochemical Gradients for Enhanced Repair of Full-Thickness Osteochondral Defect - Zhang, Liwen (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.